Investigating the Status of Communication Skills of Managers and Organizational Health of Employees in Teaching Hospitals of Shahid Sadougi University of Medical Sciences in Yazd In 2022 - Hasan Jafari; Mohammad Kazem Rahimi; Moslem Taheri Sodjani; Elahe ShisheBori (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Organizational health refers to the durability and survival of the organization in its environment, adaptation to it, as well as the promotion and development of movements for greater adaptation. Communication skills are among the skills that people can engage in. Therefore, considering the role and importance of the communication skills of managers and the organizational health of employees, the researchers decided to investigate the situation of these two variables. Methods: This cross-sectional study was conducted on all the managers and 280 employees working in the teaching hospitals of Shahid Sadoughi University of Medical Sciences in Yazd (Afshar, Shahid Rahnamon, Shahid Sadoughi, Shohada Mehrab) in 2022. The needed data were collected using standard questionnaires and analyzed in SPSS software (version 22). Descriptive statistics, including mean and standard deviation, as well as T-test and ANOVA, were used to analyze the results. Results: The results pointed out that most studied employees evaluated the level of organizational health in their hospital as high (71.6%). The highest mean in organizational health components among men was related to the morale (32.03±4.51); in women, it pertained to mood (31.86±5.07). According to the obtained results, no significant relationship was observed between hospitals, gender, age, marital status, education, service history, and organizational health components; nonetheless, a significant relationship was detected between job category and institutional unity component (P=0.003). No significant relationship was observed between the hospitals, gender, marital status, age, service history and management history, education, occupation and communication skills components of managers. The highest mean of managers' communication skills was related to feedback. Conclusion: Considering the lower mean of resource support, managerial influence, and consideration of organizational health, it seems necessary to design and implement educational and welfare programs in order to strengthen them.